Potential benefits of the application of yeast starters in table olive processing - Arroyo López, Francisco Noé; Romero Gil, Veronica; Bautista Gallego, Joaquin; Rodriguez Gomez, Francisco; Jimenez Diaz, Rufino; García García, Pedro; Querol Simon, Amparo; Garrido Fernandez, Antonio (Frontiers in Microbiology, 2012)
Yeasts play an important role in the food and beverage industry, especially in products such as bread, wine, and beer, among many others. However, their use as a starter in table olive processing has not yet been studied in detail. The candidate yeast strains should be able to dominate fermentation, together with lactic acid bacteria, but should also provide a number of beneficial advantages. Technologically, yeasts should resist low pH and high salt concentrations, produce desirable aromas, improve lactic acid bacteria growth and inhibit spoilage microorganisms. Nowadays, they are being considered as probiotic agents because many species are able to resist the passage through the gastrointestinal tract and show favourable effects on the host. In this way, yeasts may improve the health of consumers by means of the degradation of non assimilated compounds (such as phytate complexes), a decrease in cholesterol levels, the production of vitamins and antioxidants, the inhibition of pathogens, an adhesion to intestinal cell line Caco-2 and the maintenance of epithelial barrier integrity. Many yeast species, usually found in table olive processing (Wicherhamomyces anomalus, Saccharomyces cerevisiae, Pichia membranifaciens, Kluyveromyces lactis, among others), have exhibited some of these properties. Thus, the selection of the most appropriate strains to be used as starters in this fermented vegetable, alone or in combination with lactic acid bacteria, is a promising research line to develop in the near future.